TRADISI BIMBANG BEBALAI PADA ETNIS SERAWAI: SEBUAH ANALISIS FUNGSIONAL STRUKTURAL - Rois Leonard Arios (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2020)
Tradition of an ethnic group will still exist and be sustainable if the supporting communitycontinues to carry out its role in accordance with its function in the tradition. This paperexplains how bimbang bebalai tradition in the Serawai tribe, which could be implementedduring the reign, is no longer carried out even though it has been facilitated by thegovernment. In analyzing the problem, the A.R. Radcliffe-Brown structural functionalapproach was used by focusing on the analysis of the role functions of each structure. Thestudy was conducted with a qualitative approach with interviews and observations as aprimary data collection tool and supported by literature study. The study has found thatbimbang bebalai tradition cannot be implemented at this time because the existing role ofindigenous institution and structure in the tradition itself does not work. The role of thegovernment that is overboard actually eliminates the community’s role which is supposedto be facilitated as the owner and executor of the tradition.